Nursing staff attitudes to older people and dementia - Mackie, Gillian (The University of Edinburgh, 2011)
AIMS: Demographic trends indicate that the world's population is ageing. Given the increased prevalence of chronic illness and dementia with advancing age, the proportion of patients with dementia in general hospital settings is also expected to increase. Research has suggested that nurses in general medical settings can often lack specialist training, both in the care of older people and in the management of patients with dementia, as well as holding negative attitudes towards this patient group, which can impact both on the quality of care provision and the wellbeing of care providers. This study aims to explore whether nursing staff attitudes towards older people with dementia, the illness of dementia and older people differ across psychiatric and general medical settings. Given that increased knowledge and contact can support the development of positive attitudes, it was proposed that psychiatric nursing staff, who tend to have more specialist knowledge about dementia and more frequent contact with this patient group, were likely to hold more positive attitudes than general medical staff.

DESIGN/METHOD: A qualitative methodology was used and a cross -sectional between groups design was employed to compare the responses of nursing staff across psychiatric and general medical settings on a series of self -report questionnaires assessing attitudes to older people, older people with dementia, and the illness of dementia. 73 completed questionnaire packs were received (45 psychiatric; 28 general medical).

RESULTS: Nursing staff across the sample held positive attitudes towards both older people and older people with dementia; however, no significant difference in nursing staff attitudes between the psychiatric and general medical groups was reported. There was a significantly positive correlation between the attitudes nursing staff held about older people and older people with dementia across the whole sample. No significant difference was reported in nursing staff attitudes towards the illness of dementia between groups.

CONCLUSIONS: Positive attitudes towards older people and older people with dementia may be considered as reflecting the advent of a downturn in ageist attitudes in some respects; however, more research is needed to explore the manner with which such attitudes translate into practice, as well as the potential barriers to promoting positive views about older people in practice. The role of potential confounding variables in the lack of attitudinal variation between groups, such as the level of training and experience, also merits further investigation.